Value-relevance of acccounting numbers for valuation - Aba Ibrahim, Muliati; Bujang, Hajah Fatimah; Madi, Nero; Abu Samah, Aizimah; Ismai, Ummi Syarah; Jusoff, Kamaruzaman; Narawi, Azlina (David Publishing Company, USA, 2009)
Recent empirical work suggested that the ability of accounting numbers to explain the relationship between accounting numbers and stock prices has deteriorated over the past four decades. The findings of this study suggest that the accounting earnings and book value are capturing most of the information that is relevant to assess the values of firms. At the same time, it also suggests that earnings and book value as well as non-accounting beta are more valued during the financial crisis as compared to after the financial crisis. Overall, the accounting estimate of the value of the firm is not deviating from the markets' estimate, which suggests that accounting numbers play an important role in the valuation of firms in Malaysia.